Evaluation of Environmental Impacts of Traction Motor Production and Disposal - 李书华 李君 李楠楠 卢强 佟达夫 高莹 (Transactions of Tianjin University, 2013)
By the application of life cycle assessment（LCA） methodology, this paper estimates the environmental impacts of production and disposal of traction motors used in electric vehicles in China. The results show that the total energy use, the criteria emissions and the greenhouse gases（GHG） emissions of a traction motor production and disposal are about 2,899,MJ, 4.5,kg and 259.5,kg per motor, respectively. Among the regulated emissions, the SOxemission ranks first by total mass, followed by CO, PM10, NOx, PM2.5, and volatile organic compound（VOC）. The motor material production stage accounts for most of the energy consumption and emissions, followed by the assembly stage and the end-of-life disposal stage. In this study, the environmental performance analysis is extended to the comparison between the use of secondary material and primary material for the material production stage. It is found that using 100% secondary material results in a 52.9% reduction in energy consumption, a 49.8% reduction in regulated emissions, and a 49.3% reduction in GHG emissions compared with the use of 100% primary material.